Thiophene and Its Analogs as Prospective Antioxidant Agents: A Retrospective Study - Mishra, Raghav; Kumar, Nitin; Sachan, Neetu (Mini Reviews in Medicinal Chemistry, 2022)
The field of Free Radical Chemistry has gained considerable interest in the current scenario. The formation of free radicals is attributable to different physiochemical factors, radiation exposure, pathological conditions, environmental contaminants, and as by-products of metabolized drugs. The concentration of free radicals is regulated strongly under normal conditions by physiological antioxidants. Free radicals may cause oxidative damage to proteins, lipids, sugars, and DNA when abundantly produced or when antioxidants are depleted. This imbalance of reduction-oxidation, referred to as oxidative stress, can change the body's physiological conditions and ultimately lead to tissue injury, further contributing to various disease pathologies. A proper balance between free radicals and antioxidants is required for an effective physiological process. The oxidation mechanism is chemically hindered by antioxidants; these are often called free radical scavengers. The application of an external antioxidant source is crucial in addressing the issue of oxidative stress. Plenty of naturally occurring, semi-synthetic, and synthetic antioxidants are used, and the search for an efficient, non-toxic, and safe antioxidant is stepped up over time. As an influential scaffold, thiophene and its derivatives have become a significant source of interest for researchers due to its substantial variety of biological activities. The versatility of thiophene moiety has been identified by an affluent unveiling of its derivatives with anti-inflammatory, antioxidant, anti-cancer, and antimicrobial behaviors. Thiophene activity has been influenced greatly by the nature and orientation of the substitutions. The current study aims at addressing various synthetic compounds with thiophene or condensed thiophene as a fundamental moiety or substituent as radical scavengers.
Keywords: analogues